Chemical glycobiology. - Imperiali, Barbara (Methods in enzymology, 2018)
Chemical Glycobiology, Part B, Volume 598, the latest release in the Methods in Enzymology series, continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume is the second release on chemical glycobiology.